Home-Based HIV Testing Among Pregnant Couples Increases Partner Testing and Identification of Serodiscordant Partnerships. (1st August 2016) - Krakowiak, Daisy; Kinuthia, John; Osoti, Alfred O.; Asila, Victor; Gone, Molly A.; Mark, Jennifer; Betz, Bourke; Parikh, Saloni; Sharma, Monisha; Barnabas, Ruanne; Farquhar, Carey
Abstract : Introduction: Male partner HIV testing has been recognized as an important component of prevention of mother-to-child HIV transmission. Scheduled home-based couple HIV testing may be an effective strategy to reach men. Methods: Women attending their first antenatal visit at Kisumu County Hospital in Kenya were randomized to home-based education and HIV testing within 2 weeks of enrollment (HOPE) or to written invitations for male partners to attend clinic (INVITE). Male partner HIV testing and maternal child health outcomes were compared at 6 months postpartum. Results: Of 1101 women screened, 620 were eligible and 601 were randomized to HOPE (n = 306) or INVITE (n = 295). At 6 months postpartum, male partners were more than twice as likely [relative risk (RR) = 2.10; 95% CI (CI): 1.81 to 2.42] to have been HIV tested in the HOPE arm [233 (87%)] compared with the INVITE arm [108 (39%)]. Couples in the HOPE arm [192 (77%)] were 3 times as likely (RR = 3.17; 95% CI: 2.53 to 3.98) to have been tested as a couple as the INVITE arm [62 (24%)] and women in the HOPE arm [217 (88%)] were also twice as likely (RR = 2.27; 95% CI: 1.93 to 2.67) to know their partner's HIV status as the INVITE arm [98 (39%)]. More serodiscordant couples were identified in the HOPE arm [33 (13%)] than in the INVITE arm [10 (4%)] (RR = 3.38; 95% CI: 1.70 to 6.71). Maternal child health outcomes of facility delivery, postpartum family planning, and exclusive breastfeeding did not vary by arm. Conclusions: Home-based HIV testing for pregnant couples resulted in higher uptake of male partner and couple testing, as well as higher rates of HIV status disclosure and identification of serodiscordant couples. However, the intervention did not result in higher uptake of maternal child health outcomes, because facility delivery and postpartum family planning were high in both arms, whereas exclusive breastfeeding was low. The HOPE intervention was successful at its primary aim to increase HIV testing and disclosure among pregnant couples and was able to find more serodiscordant couples compared with the invitation-only strategy. Trial Registration: Clinicaltrials.gov registry: NCT01784783.